SAT0317 INCIDENCE OF EXTRA-ARTICULAR MANIFESTATIONS IN ANKYLOSING SPONDYLITIS, PSORIATIC ARTHRITIS AND UNDIFFERENTIATED SPONDYLOARTHRITIS – RESULTS FROM A NATIONAL REGISTER-BASED COHORT STUDY. (June 2019) - Bengtsson, Karin; Forsblad-D'elia, Helena; Klingberg, Eva; Lindström, Ulf; Dehlin, Mats; Exarchou, Sofia; Deminger, Anna; Askling, Johan; Jacobsson, Lennart T.H.
Abstract : Background: Spondyloarthritis (SpA), including ankylosing spondylitis (AS), psoriatic arthritis (PsA) and undifferentiated SpA (uSpA), are all to varying degrees associated with extra-articular manifestations (EAMs). Objectives: To estimate incidence rates (IRs) for EAMs (anterior uveitis, inflammatory bowel disease (IBD) and psoriasis) in patients with AS, PsA and uSpA, respectively. Methods: In this nationwide cohort study, three separate cohorts of patients aged 18 to 69 years with AS (n=8517, 68% men, mean age 47±13 years), PsA (n=22667, 46% men, mean age 49±12 years) and uSpA (n=10245, 44% men, mean age 42±13 years) were identified 2001-2015 in the Swedish National Patient Register (NPR). The follow-up began 1 January 2006, or six month after the date of the first SpA diagnosis thereafter in previously undiagnosed cases, and ended at the first date of EAM, death, emigration or 31 December 2016, respectively. Both the SpA diagnoses and EAMs were identified according to specified ICD codes. Number of outcomes, person-years at risk and IRs with 95% CI were calculated for each EAM and stratified by sex and age-intervals. Patients with a prior EAM in NPR before start of follow-up were excluded from that specific analysis. Results: The IRs for each EAM are presented in Table 1 . The overall highest IRs were noted for anterior uveitis in patients with AS (14.4 (13.2-15.5) per 1000 person-years at risk). Patients with PsA had considerably lower IRs for anterior uveitis (1.7 (1.5-1.9) per 1000 person-years at risk) and slightly lower IRs for IBD than patients with AS and uSpA. The IRs for anterior uveitis were significantly higher in men than in women in both AS and uSpA. Conclusion: IRs for EAMs clearly differed between the SpA subtypes, and especially for anterior uveitis where the IRs were by far highest in patients with AS and uSpA compared to patients with PsA. Disclosure of Interests: Karin Bengtsson: None declared, Helena Forsblad-d'Elia Grant/research support from: Unrestricted grants from Novartis outside the submitted work, Consultant for: Advisory board fees from Sandoz, Novartis and Abbvie, Speakers bureau: Lecturing fees from Novartis, Eva Klingberg Grant/research support from: Unrestricted grant from Roche, Consultant for: Novartis, Speakers bureau: Speakers fee from Lilly, Ulf Lindström: None declared, Mats Dehlin: None declared, Sofia Exarchou: None declared, Anna Deminger: None declared, Johan Askling Grant/research support from: Karolinska Institutet (JA) has or has had research agreements with the following pharmaceutical companies, mainly in the context of the ATRIS national safety monitoring programme for rheumatology biologicals: Abbvie, BMS, MSD, Eli Lilly, Pfizer, Roche, Samsung Bioepis, and UCB., Consultant for: Karolinska Institutet has received remuneration for JA participating in ad boards arranged by Lilly, Novartis, and Pfizer., Lennart T.H. Jacobsson Consultant for: LJ has received lecture and consulting fees from Pfizer, Abbvie, Novartis, Eli-Lily and Janssen